Diagnostic Accuracy of Magnetic Resonance Cholangiopancreatography in the Detection of Choledocholith, taking Post-Operative findings as the Gold Standard - Ayesha Javaid; Rashid Mahmood; Hidayat Ullah; Mazhar Shafiq; Nazia Dildar; Ghulam Abbas (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the diagnostic accuracy of Magnetic resonance cholangiopancreatography (MRCP) in the detection of Choledocholith, taking post-operative findings as the gold standard.